DA’WAH AMONG URBAN MUSLIMS IN INDONESIA - Rini Setiawati; Dede Mercy Rolando; Robby Aditya Putra; Osman Koroglu (Akademika : Jurnal Pemikiran Islam, 2022)
The condition of da'wah portraits in the current era of information globalization which is increasingly heavy and complex is certainly a challenge for the development of da'wah. The emergence of problems that target the younger generation is a point of threat to the survival of Muslims, especially in Indonesia. This study aims to look at the portrait of the current da'wah problem and its strategy. The type of research used is a literature review. The results obtained are portraits of the problems faced and become challenges and threats for da'wah activists and da'i namely "silting of faith" due to the progress of the times such as problems related to the erosion of Faith and Manner, shifts in the authority of a single religion, problems of pluralistic, hedonistic, individualistic society. towards a materialistic society associated with rationalistic Muslims. The characteristics of the profile of the Indonesian Muslim community have caused problems both internally and externally. So that this reality requires the application of an effective and efficient da'wah strategy by linking the elements of preachers, messages as well as media in order to compete and maintain Islamic values ​​in the midst of the threat of the times by improving the quality in terms of substantive and methodological competence, increasing the values ​​of rahmatan lil alamin and universal values ​​and the importance of mastering information technology with the use of media up-to-date.